2006
DOI: 10.1007/s10681-006-9182-8
|View full text |Cite
|
Sign up to set email alerts
|

More precise map position and origin of a durable non-specific adult plant disease resistance against stripe rust (Puccinia striiformis) in wheat

Abstract: Recently a major gene determining non-specific adult plant disease resistance against stripe rust (Puccinia striiformis) designated Yrns-B1 was mapped in wheat Triticum aestivum L. by using a cross between 'Lgst. 79-74' (resistant) and 'Winzi' (susceptible). Linkage to five Gatersleben wheat microsatellite (GWM) markers was discovered, previously mapped on chromosome arm 3BS. In the present study this map was improved by the incorporation of four additional GWM markers. QTL-analysis revealed high LOD values fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 25 publications
(26 reference statements)
4
22
0
Order By: Relevance
“…An F 2 population from a cross between PI178383 and Harmankaya99 was visually assessed for seedling infection type in greenhouse. Similar to our work, Khlestkina et al (2007) identified Xgwm533 as a diagnostic marker for disease resistance against yellow rust in spring wheat. The 117 bp allele of Xgwm533 was found in about 35 % of the cultivars analysed, however, none of them possessed the expected disease resistance.…”
Section: Discussionsupporting
confidence: 88%
“…An F 2 population from a cross between PI178383 and Harmankaya99 was visually assessed for seedling infection type in greenhouse. Similar to our work, Khlestkina et al (2007) identified Xgwm533 as a diagnostic marker for disease resistance against yellow rust in spring wheat. The 117 bp allele of Xgwm533 was found in about 35 % of the cultivars analysed, however, none of them possessed the expected disease resistance.…”
Section: Discussionsupporting
confidence: 88%
“…QTL validation for different rust diseases caused by Puccinia sp. has been carried out in wheat (Khlestkina et al 2007;Schnurbusch et al 2004), barley (Castro et al 2003), and sugar cane (McIntyre et al 2005) to name a few. In all cases a major locus conferring resistance to the rust disease was found and its presence validated across unrelated pedigrees.…”
Section: Discussionmentioning
confidence: 99%
“…QTLs on 3BS have been identified by Singh et al (2000b), Suenaga et al (2003) and Khlestkina et al (2007) and on 3BL by Lin and Chen (2009). It seems highly likely that the 3BS QTL of Khlestkina et al (2007) and Singh et al (2000b) are at the same locus as they are flanked by a common SSR marker locus (Xgwm533.2). Furthermore, all of the other markers defining these QTLs have close linkage with each other across many genetic maps.…”
Section: Group 3 Qtlsmentioning
confidence: 99%
“…Furthermore, all of the other markers defining these QTLs have close linkage with each other across many genetic maps. For example, in the ITMI mapping population, the marker locus Xfba190 in Singh et al (2000b) maps closely to marker loci (Xgwm389 and Xgwm533) defining the ) QTL, as well as the marker loci (Xgwm493 and Xgwm533) of the Khlestkina et al (2007) QTL. The markers defining the 3BL locus of Lin and Chen (2009) are not associated in any maps with the 3BS markers.…”
Section: Group 3 Qtlsmentioning
confidence: 99%